Contemporary Western Scholarship on Islam: An Appraisal of Selected ‘Introductory’ Reference Works on Islamic History - Parray, Tauseef Ahmad (Balai Penelitian dan Pengembangan Agama Semarang, 2021)
Writing on Islamand things Islamic has a long history in the West, but has seen a growth in 20thcentury and an unprecedented surgeafter the events of 9/11 (2001)—both because of Islam’s ‘global’ spread and ‘growing global impact’ as well as its diverse interpretations and explanations. Among this plethora of literature, a major portion is devoted to the Islamic historyand its inter-related aspects, in the form of ‘introductory’ reference books.These are primarily targeted for (under) graduate student community as well as for the general people interested in knowing about the faith and beliefs of 1.6 billion Muslims, living globally. This study, in this context, attempts to present an evaluation and brief content-analysis of four (4) latest works by the Western academics (mostly ‘Islamicists’) on Islamic history, published in between 2009 and 2016 (and referring to their latest editions as well). Theoretical in nature, following both descriptive and comparative methodological approaches, this study attempts to (i) get clues of the recent trends, tendencies and tenors in the English (predominantly American) scholarship on Islamic history; and (ii) identify the main topics, themes and issues covered under the broader rubric ofIslamic history/ civilization in these works. The study agrues that such mins of appraisal and evaluation helps in understanding the main themes/ topics discussed under the broader rubric ofIslamic historyas well as helps in knowing and understanding the diverse scholarly approaches adopted in studying different aspects of Islamic history—from classical to contemporary eras.